THE IMPACT OF FINANCIAL DEVELOPMENT ON RENEWABLE ENERGY CONSUMPTION IN KENYA - Mercy T Musakwa; Nomfundo P Vacu; Nicholas M Odhiambo (Acta Economica)
Purpose: Increasing awareness of global warming consequences, together with the call for all countries to take responsibility for reducing their carbon footprint by moving to cleaner energy use motivated this study to examine the impact of financial sector development on renewable energy for Kenya. The study aims to answer the question, ‘Can financial sector development help Kenya to increase renewable energy consumption?’ The study used annual data from 1990 to 2020 to examine the nature of the relationship between the two variables. Methodology: The study employed autoregressive distributed lag (ARDL) approach. Results: The study found financial development to have a positive impact on renewable energy consumption in the short and long run. Conclusions: The results point to the significant role that the financial sector plays in availing resources for cleaner energy projects. Recommendations: Policymakers in Kenya should harness the country’s financial sector potential to meet the Sustainable Development Goals aligned to cleaner energy consumption.